Greenshield Neem: Microencapsulation Formulation of Neem Leaves as a Sustainable Agricultural Technology for Indonesia 2045 - Sulisatun Nisak; Aisyah Humairah; Retno Leodita Lubis (Penerbit Goodwood, 2026)
Purpose: This study proposes GreenShield Neem, a microencapsulated neem (Azadirachta indica A. Juss) formulation, as a sustainable biopesticide technology to support environmentally friendly agriculture in Indonesia toward the 2045 vision. Research Methodology: This study used a structured literature review and a conceptual synthesis. Peer-reviewed articles published between 2014 and 2024 were screened; 42 records were initially identified, and 26 articles were selected for an in-depth review based on predefined inclusion/exclusion criteria. Data analysis was conducted using thematic coding and comparative synthesis by extracting key variables (formulation type, encapsulation method/materials, stability indicators, controlled release behavior, and reported bioefficacy). The extracted evidence was then consolidated to develop the GreenShield Neem conceptual framework and a proposed field-application scenario. Results: The literature synthesis indicates that neem-based biopesticides possess strong insecticidal properties due to bioactive compounds such as azadirachtin, salannin, and nimbin. However, conventional neem formulations suffer from low stability. Microencapsulation technology significantly enhances the stability, persistence, and efficacy of these bioactive compounds by protecting them against ultraviolet radiation, oxidation, and environmental degradation, while enabling their controlled release in the field. Conclusions: GreenShield Neem demonstrates strong potential as a sustainable pest-management innovation that can reduce dependence on synthetic pesticides, minimize environmental contamination, and improve the efficiency of agricultural practices. Limitations: This study is limited to a conceptual, literature-based analysis and lacks experimental validation. Contributions: This article advances sustainable agriculture by offering a scientifically grounded formulation concept that integrates local biological resources with modern delivery technologies, particularly for tropical agricultural systems.